2019
DOI: 10.3390/foods8010023
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Some Microbiological and Chemical Features in Herby Cheese

Abstract: The objective of this study is to measure the amounts of biogenic amines, microbial counts, values of pH, titratable acidity, dry matter, and salt (%) in herby cheese, a very popular staple in the Turkish diet, and to evaluate the concentration of biogenic amines in terms of public health risks. A high-performance liquid chromatography (HPLC) method was used for the determination of eight biogenic amines in 100 herby cheeses sold in the local markets of Van. The bacterial load of the herby cheeses ranged betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
1
13
2
Order By: Relevance
“…Sagun et al [52], reported that the concentration of histamine gradually increased during ripening from 21.90 mg•kg −1 on the first day to 46.20 mg•kg −1 after 3 months. The amounts of tyramine found in the Herby cheeses were up to 725.21 mg•kg −1 [51] and 1125.50 mg•kg −1 [53]. In our study, histamine contents were higher in all cheese models examined compared to tyramine levels.…”
Section: Contents Of Biogenic Amines In the Analyzed Cheese Modelssupporting
confidence: 38%
See 1 more Smart Citation
“…Sagun et al [52], reported that the concentration of histamine gradually increased during ripening from 21.90 mg•kg −1 on the first day to 46.20 mg•kg −1 after 3 months. The amounts of tyramine found in the Herby cheeses were up to 725.21 mg•kg −1 [51] and 1125.50 mg•kg −1 [53]. In our study, histamine contents were higher in all cheese models examined compared to tyramine levels.…”
Section: Contents Of Biogenic Amines In the Analyzed Cheese Modelssupporting
confidence: 38%
“…Histamine and tyramine are described as the most abundant biogenic amines in cheeses made of cow and sheep milk [9,43]. The amount of histamine found in the Herby cheese samples tested by Ekici et al [51] ranged from <0.033 to 469.00 mg•kg −1 . Sagun et al [52], reported that the concentration of histamine gradually increased during ripening from 21.90 mg•kg −1 on the first day to 46.20 mg•kg −1 after 3 months.…”
Section: Contents Of Biogenic Amines In the Analyzed Cheese Modelsmentioning
confidence: 97%
“…In recent years, studies on Herby cheese consisted mainly of the production technique of Herby cheese (Coşkun, 1995; 2005; Emirmustafaoğlu & Coşkun, 2012; Hayaloğlu & Fox, 2008; Tarakci & Temiz, 2009), the effect of different herbs on the composition of Herby cheese (Andic, Tuncturk, Javidipour, & Genccelep, 2015; Coşkun & Tunçtürk, 2000; Kavaz, Bakırcı, & Kaban, 2013; Tarakci, Durmaz, & Sagun, 2005; Tarakci & Kucukoner, 2006; Tarakci, Temiz, Aykut, & Turhan, 2011), comparison of Herby cheese produced by traditional and industrial methods (Kose & Ocak, 2019; Ocak, Javidipour, & Tuncturk, 2014; Tuncturk, Ocak, & Kose, 2014), and researches of Herby cheese samples obtained from the market (Andic et al., 2010; Ekici, Okut, İşleyici, Sancak, & Tuncay, 2019; Eralp, 1953; Hayaloglu & Karabulut, 2013; Isleyici, 1999; İsleyici & Akyuz, 2009; Koyuncu & Tuncturk, 2020; Kurt, 1968; Kurt & Akyüz, 1984; Ocak & Köse, 2010; 2018; Ozcan, Yılmaz‐Ersan, Akpinar‐Bayizit, & Delikanli‐Kiyak, 2017; Ozrenk, Kose, & Ekin, 2009; Sancak, 1989; Sancak, Boynukara, & Yardımcı, 1993; Sönmezsoy, 1994; Tuncay & Sancak, 2018). Researches on Herby cheese samples obtained from the market were also evaluated with some routine and physical, chemical properties, and microbiological aspects of Herby cheese samples.…”
Section: Introductionmentioning
confidence: 99%
“…Biogenic amines (BAs) are organic bases with an aliphatic, aromatic, or heterocyclic structure which have been found in many foods, such as fishery products, cheese, wine, beer, and other fermented foods [1,2]. The term ''biogenic amines" defines decarboxylation products such as histamine, serotonin, tyramine, phenylethylamine, tryptamine, and also aliphatic polyamines and can be ubiquitously synthesised from their aminoacidic precursors [3].…”
Section: Introductionmentioning
confidence: 99%